2020
DOI: 10.7554/elife.55966
|View full text |Cite
|
Sign up to set email alerts
|

A dynamic charge-charge interaction modulates PP2A:B56 substrate recruitment

Abstract: The recruitment of substrates by the ser/thr protein phosphatase 2A (PP2A) is poorly understood, limiting our understanding of PP2A-regulated signaling. Recently, the first PP2A:B56 consensus binding motif, LxxIxE, was identified. However, most validated LxxIxE motifs bind PP2A:B56 with micromolar affinities, suggesting that additional motifs exist to enhance PP2A:B56 binding. Here, we report the requirement of a positively charged motif in a subset of PP2A:B56 interactors, including KIF4A, to facilitate B56 b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
51
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 41 publications
(51 citation statements)
references
References 59 publications
0
51
0
Order By: Relevance
“…This R2 region includes a higher density of positively charged residues that enhance binding most likely via charged:charged interactions. Indeed, this has also been recently shown for protein phosphatase 2B (PP2B; PP3; Calcineurin) and the B56 regulatory subunit of PP2A, where these dynamic charged:charged interactions were shown to play a role in substrate specificity (Hendus-Altenburger et al, 2019;Wang et al, 2020). Thus, such interactions, which have been recently recognized to be critical for the interaction of IDPs with their target proteins and allow for increased entropy, are likely important for substrate recruitment and specificity by different phosphatases.…”
Section: Discussionmentioning
confidence: 74%
“…This R2 region includes a higher density of positively charged residues that enhance binding most likely via charged:charged interactions. Indeed, this has also been recently shown for protein phosphatase 2B (PP2B; PP3; Calcineurin) and the B56 regulatory subunit of PP2A, where these dynamic charged:charged interactions were shown to play a role in substrate specificity (Hendus-Altenburger et al, 2019;Wang et al, 2020). Thus, such interactions, which have been recently recognized to be critical for the interaction of IDPs with their target proteins and allow for increased entropy, are likely important for substrate recruitment and specificity by different phosphatases.…”
Section: Discussionmentioning
confidence: 74%
“…1D). As an example, Kif4A T799 and ADAM17 T735 are known targets of PP2A-B56 and these two proteins contain validated LxxIxE motifs (Bastos et al, 2014;Kruse et al, 2020;Wang et al, 2020). Furthermore, RacGAP1 S203, BubR1 T508 and ESPL1 S1475 are close to validated LxxIxE motifs supporting the strength of the screening approach.…”
Section: A Screen For Pp2a-b56 Mitotic Substrates Identifies Cdc20mentioning
confidence: 72%
“…It was recently shown that a subset of PP2A-B56 interactors harbour a positively charged motif, complementary to an acidic patch on B56 34 . Deltaretroviral INs do not engage with this acidic patch but appear to have evolved to use an interface employed by other PP2A-B56 interactors, like BUBR1 and CHK2 (Supplementary Fig.…”
Section: Discussionmentioning
confidence: 99%